2017
DOI: 10.1016/j.ymthe.2017.07.004
|View full text |Cite
|
Sign up to set email alerts
|

Long-Duration Complete Remissions of Diffuse Large B Cell Lymphoma after Anti-CD19 Chimeric Antigen Receptor T Cell Therapy

Abstract: T cells expressing anti-CD19 chimeric antigen receptors (CARs) can induce complete remissions (CRs) of diffuse large B cell lymphoma (DLBCL). The long-term durability of these remissions is unknown. We administered anti-CD19 CAR T cells preceded by cyclophosphamide and fludarabine conditioning chemotherapy to patients with relapsed DLBCL. Five of the seven evaluable patients obtained CRs. Four of the five CRs had long-term durability with durations of remission of 56, 51, 44, and 38 months; to date, none of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
186
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 246 publications
(200 citation statements)
references
References 40 publications
6
186
1
1
Order By: Relevance
“…21 in published clinical trials. [1][2][3][4][5][6][7][8][9][10][11][12][13]30,[37][38][39][40][41][42][43][44] By administering diminishing doses of CAR19 T cell products with similar phenotype, including CD4:CD8 ratios, we found 4-1BB co-stimulation led to greater potency and control of repeat doses of B-ALL. These results are most likely a product of 4-1BB co-stimulation promoting longer CAR19 T cell persistence than CD28, a finding consistent with other pre-clinical studies [45][46][47] and clinical trials.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…21 in published clinical trials. [1][2][3][4][5][6][7][8][9][10][11][12][13]30,[37][38][39][40][41][42][43][44] By administering diminishing doses of CAR19 T cell products with similar phenotype, including CD4:CD8 ratios, we found 4-1BB co-stimulation led to greater potency and control of repeat doses of B-ALL. These results are most likely a product of 4-1BB co-stimulation promoting longer CAR19 T cell persistence than CD28, a finding consistent with other pre-clinical studies [45][46][47] and clinical trials.…”
Section: Discussionmentioning
confidence: 85%
“…These results are most likely a product of 4-1BB co-stimulation promoting longer CAR19 T cell persistence than CD28, a finding consistent with other pre-clinical studies [45][46][47] and clinical trials. [2][3][4][5][6][7][8][9][10][11][12][13]37,40,44 Regardless of co-stimulatory domain, our final piggy-Bac-generated CAR19 T cell products all displayed a predominantly differentiated phenotype with elevated immuno-inhibitory markers. This may result from ex vivo expansion via repeated CAR stimulation.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…As in the first group, acute toxicities generally resolved within 3 weeks after cell infusion. In a long-term follow up study of these patients, duration of 4 of the 5 CRs ranged from 38þ to 56þ months [39]. More recently, the NCI, with research support from Kite Pharma, reported similar results with anti-CD19 CAR T cell therapy and low-dose conditioning like that used in the ZUMA-1 trial (300 or 500 mg/m 2 of cyclophosphamide and 30 mg/m 2 of fludarabine, each given daily on days À5, À4, and À3) in 22 patients with aggressive B cell lymphomas (19 with DBLCL, 2 with TFL, 1 with mantle cell lymphoma) [32].…”
Section: Initial Clinical Experience With Car T Cells In B Cell Maligmentioning
confidence: 99%
“…Intravenous substitution of immunoglobulin can help to reduce this risk. While sustained B-cell aplasia has been primarily reported in pediatric B-ALL patients [42,43], 2 studies in adult B-NHL patients have demonstrated that recovery of humoral immunity is possible following anti-CD19 CAR T-cell therapy even in the setting of ongoing CR [44,45].…”
Section: Clinical Outcomes and Adverse Eventsmentioning
confidence: 99%